Melacak Akar Perang Suci: Perkembangan Ide Jihād dalam Tradisi Islam - Ismatu Ropi (Refleksi: Jurnal Kajian Agama dan Filsafat, 2002)
This article examines Reuven Firestone’s book, Jihad: The Origin of Holy War in Islam (New York: Oxford University Press, 1999), within the broader context of the historical and scholarly discourse on religious wars. The study of holy war as a religiously justified conflict remains relatively new in academic traditions, with early foundational works such as Julius Wellhausen’s Prolegomena to the History of Ancient Israel (1885) inspiring later research. Comparative studies on the Judeo-Christian tradition have been explored by scholars such as Susan Niditch, Roland Bainton, and James A. Brundage. Meanwhile, Western scholarly attention to religious war in Islam began in the early 20th century with works by Gardner (1912) and Stephen van Rensselaer Trowbridge (1913), followed by seminal studies such as Majid Khadduri’s War and Peace in the Law of Islam (1955) and Rudolph Peters’ Jihad in Mediaeval and Modern Islam (1977). The term "holy war" itself remains problematic, as its definition is contested and varies across different traditions. In the European context, it is often framed as a form of justification for war through religious legitimacy. Unlike conventional warfare, which is based on strategy, military strength, and tactical calculations, religious war often involves eschatological, metaphysical, and supernatural elements. Historical examples, such as the Battle of Badr, illustrate how religious narratives influence perceptions of divine intervention in warfare. The article also addresses the paradox of how religions, which fundamentally advocate order and morality, justify violence. Drawing on political, theological, and linguistic perspectives, it argues that religious war functions within a binary opposition framework, where good confronts evil and divine forces oppose satanic ones. Within this paradigm, material motivations become secondary to spiritual rewards, including divine favor and the promise of paradise. This study contributes to the ongoing debate on the ideological and theological dimensions of religious war, particularly in the Islamic tradition.